Compatible Donor and Recipient Pairs’ Perspectives on Participation in Kidney Paired Donation Programs: A Mixed-Methods Study - Marie-Chantal Fortin (SAGE Publishing, 2021)
Background: Compatible pair participation in kidney paired donation (KPD) may increase the likelihood of finding suitable matches for all registered pairs. Retrospective studies have shown variable enthusiasm for participating in KPD in compatible pairs. Objective: The study objective was to gather potential living donor (PLD) and transplant candidate (TC) perspectives on compatible pair participation in KPD. Design: Surveys and qualitative interviews. Setting: Three transplant programs in Canada: Centre hospitalier de l’Université de Montréal in Montreal (Québec), Vancouver General Hospital, and St. Paul’s Hospital in Vancouver (British Columbia). Patients: Both PLDs and TCs undergoing evaluation for donation/transplantation between 2016 and 2018 at 3 transplant programs in Canada. Methods: Descriptive statistical analysis was performed for the results of the survey and thematic and content analysis method was used for the content of the qualitative interviews. Results: A total of 116 PLDs and 111 TCs completed surveys and an additional 18 PLDs and 17 TCs underwent semi-directed interviews. Of those surveyed, 61.2% of PLDs and 76.6% of TCs reported a willingness to participate in KPD as a compatible pair. The possibility of a more optimally matched kidney for the TC and policies ensuring prioritization of the TC for repeat transplantation in the event of early graft failure increased willingness to participate in KPD. Major concerns expressed during the interviews included the desire to retain the emotional bond of directed donation, the fear of chain breaks or donor reneging, delays in transplantation, and additional travel associated with participation in KPD. Limitation: The limitations of this study are that it was conducted in only 3 Canadian transplant programs and that the interviews and surveys were in French and in English. As a consequence, the results may not be reflective of the views of individuals not living in these 2 provinces and from ethnic minority populations. Conclusion: Most of the compatible PLDs and TCs surveyed were willing to participate in KPD. Ensuring timely transplantation and a more optimal match for TCs and offering a policy of reciprocity to ensure timely repeat transplantation for compatible recipients if their allograft fails post KPD transplant may further increase compatible pair participation in KPD.